Penetapan Hari Pernikahan Berdasarkan Tradisi Jujuran - Sitompul, Elma Ariska; Nasution, Muhammad Arsad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Godhead. In Islamic marriage law, there is a principle known as the principle of selectivity.The problems in this thesis are how to determine the wedding day based on the Jujuran tradition in Hutabalang Village, and How to Review Islamic Law on the determination of the wedding day based on the Jujuran tradition in Hutabalang Village. The purpose of this study was to determine the implementation of determining the wedding day based on the Jujuran tradition in Hutabalang Village, and to analyze the Islamic Law Review on the determination of the wedding day based on the Jujuran tradition in Hutabalang Village, Badiri District, Central Tapanuli Regency.This type of research is field research using qualitative descriptive analysis method. This research approach is by means of observation, interviews, documentation based on the provisions of Islamic law and applicable customary law relating to the determination of a wedding day based on the jujuran tradition in Hutabalang Village, Badiri District, Central Tapanuli Regency. As for what the researchers studied were traditional leaders, religious leaders, and communities who determined their wedding day based on the jujuran tradition.The results showed that